ANALISA KEPUASAN PELANGGAN PADA BYREQUEST CRAFT ART STUDIO - Aulia Dynda Eka Mayasari (PUTRA JAWA PUBLISHER, 2023)
Entrepreneurship thrives on human creativity, giving rise to various enterprises like Byrequest Craft Art Studio, a venture operating under CV. Sarana Bahagia. This studio specializes in crafting customized dowry items and ring boxes for couples in Surabaya. Positioned to cater to the unique demands of clients, this venture anticipates substantial public interest, especially in remote regions of Indonesia, where individuals seek both quality and affordability. Furthermore, this discussion highlights the critical role of business ethics, particularly the principle of honesty, in sustaining companies, including service-oriented entities. It emphasizes transparency, integrity, and honesty throughout their operations. The focus of our analysis is on the importance of business ethics in terms of honesty in product and service descriptions, transparent promotional practices, the delivery of promised services, and the consistent application of ethical conduct. These practices cultivate customer trust and loyalty, thereby enhancing a company's long-term success in a competitive market and promoting ethical business standards for the betterment of society.